8 - La diaspora africaine et l’identité biculturelle : enjeux et défis pour la réinvention de l’Afrique - Bazonzi, José Mvuezolo (Africa Development, 2021)
Africa has a trained diaspora, with diverse skills and likely to play a key role in its development. Up to now, observation has shown that the action of diaspora associations in favor of the continent remains remarkable, through remittances, social economy activities (urban transport, development of micro-finance, social buildings, cooperatives, etc.) and the renewal of basic socio-economic infrastructure (schools, health centers, etc.). While these initiatives are commendable and encouraging, there is a glaring lack of organization of this diaspora as an entity endowed with a specific awareness and identity as a community attached to their home region and, in one way or another, liable for concrete actions for the reinvention of Africa. This reinvention necessarily involves the development of a bicultural identity capable of forging, re-forging and strengthening forever transnational and transgenerational ties with the continent. The biculturality discussed here should focus on two key elements: the genesis of a new culture and integral development. The first part of this vast and ambitious program on the process of Africa’s reinvention suggests the very reinvention of a new culture which is neither entirely African nor totally foreign but which falls between the two aforementioned and would be enriched by the contributions of both cultures (example: the role of technological socialization in the Asian cultural model). The second part seeks to rethink the continent’s development (the crucial role of education and work in the Western model). This paper proposes to revisit the possibilities offered by the cultural diversity of the African continent in order to instill in the diaspora a new cultural identity, while highlighting the various issues and challenges of this biculturality for the reinvention of Africa. Theoretical materials (A. Mabogunje’s systemic approaches and D. Massey’s transnational networks) and empirical materials drawn from the African, Asian (Japanese, Chinese and Korean) and Western cultures will be usefully mobilized to support the thesis of bicultural identity.